Main conceptual provisions of the creation of an electronic state register of immovable cultural heritage of Ukraine. Part 1 - Chabaniuk, V.; Dyshlyk, O.; Polyvach, K.; Pioro, V.; Kolimasov, I.; Nechyporenko, J. (Land Management, Cadastre and Land Monitoring, 2022)
Annotation. To organize the creation of a new modern electronic State Register of Immovable Cultural Heritage (CH) of Ukraine, it is proposed to use a methodology based on the so-called Solutions Frameworks (SoFr) "something" = X, where X denotes both the specified system (subsystem) and class of such systems (subsystems). The application of SoFr to X entirely is called the main conceptual position 0 in the article, but despite its obviousness, the epigraph is applicable to the construction of X SoFr: “The hardest thing is to see what is right in front of you. - Goethe» [1; Preface]. X in the X SoFr record takes the meaning of a hierarchically structured Atlas Geoinformation System (AGIS), consisting of four strata (bottom-up ): Operational (w), Application (a), Conceptual (b) and General (g). X SoFr in the article takes three meanings: SoFr AGIS1 (defines the activity of creating the first stage of AGIS - AGIS1 = X), aSoFr AGIS1 (defines the activity "between" subsystems AGIS1 Application and Operational strata top-down ¯), bSoFr AGIS1 determines the activity "between" the subsystems of AGIS1 Conceptual and Application strata from top to bottom ¯). X SoFr is determined by the packages and the relation between them, the so-called "petrad" of Publication-Products-Processes-Basics-Services. Packages Products-Processes-Basics and the relation between them are called the main triad of SoFr. This triad is the basis of the main conceptual provisions 1-3. They are formulated as follows: SoFr.Products - provision 1, SoFr.Processes - provision 2, SoFr.Basics - provision 3. Part 1 describes the introduction to the problem and provisions 0 and 1. Provisions 2, 3 are described in Part 2. The methodology, based on the Solutions Frameworks, implements a specific systematic approach to creating a new modern electronic State Register of Immovable Cultural Heritage of Ukraine.